2009
DOI: 10.1371/journal.pone.0004224
|View full text |Cite
|
Sign up to set email alerts
|

Conidiation Color Mutants of Aspergillus fumigatus Are Highly Pathogenic to the Heterologous Insect Host Galleria mellonella

Abstract: The greater wax moth Galleria mellonella has been widely used as a heterologous host for a number of fungal pathogens including Candida albicans and Cryptococcus neoformans. A positive correlation in pathogenicity of these yeasts in this insect model and animal models has been observed. However, very few studies have evaluated the possibility of applying this heterologous insect model to investigate virulence traits of the filamentous fungal pathogen Aspergillus fumigatus, the leading cause of invasive aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 82 publications
(93 reference statements)
6
71
1
3
Order By: Relevance
“…15,25 Dose-dependent mortality observed in this study was expected, as it has also been shown in studies carried out with A. fumigatus. 25 This, plus the obvious development of hyphae inside the larval body, indicates that A. terreus kills larvae through an active infection mechanism rather than a merely physical effect of the injected conidia. Similar to what has been shown in 2 different mouse models and embryonated chicken eggs, higher doses of A.terreus conidia were necessary to cause same lethality compared to A. fumigatus in larvae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…15,25 Dose-dependent mortality observed in this study was expected, as it has also been shown in studies carried out with A. fumigatus. 25 This, plus the obvious development of hyphae inside the larval body, indicates that A. terreus kills larvae through an active infection mechanism rather than a merely physical effect of the injected conidia. Similar to what has been shown in 2 different mouse models and embryonated chicken eggs, higher doses of A.terreus conidia were necessary to cause same lethality compared to A. fumigatus in larvae.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, investigating putative differences in virulence potential of A. fumigatus color mutants did not reveal any correlation between faster germination and higher pathogenicity. 25 Different outcome of infection is also linked to variable response of immune cells, such as killing of intruding pathogens by phagocytic cells, as shown in this study. Reasons therefore could be explained by variations in the outer layers of the isolates or to a difference in resistance to killing by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 61%
“…Galleria mellonella larvae in the final larval stage (Vanderhorst Wholesale, Inc., St. Marys, OH) were inoculated on the same day of their arrival. Larvae (15 per strain) were inoculated with 5 l of conidial suspension (2 ϫ 10 7 conidia/ml) as described elsewhere (28,29) and incubated at 37°C. Mortality was scored based on color change (from pale beige to dark brown or black) and unresponsiveness to tactile stimulus.…”
Section: Growthmentioning
confidence: 99%
“…First, we compared the survival of larvae of G. mellonella infected with the sRNA mutant and the corresponding complemented strains with those infected with the wild type. Infection of G. mellonella worms has emerged as a reliable model system to study the pathogenesis of numerous human pathogens (60)(61)(62)(63)(64)(65)(66). Indeed, the growth of the larvae at 37°C and the high degree of structural and functional homology between the innate immune systems of Galleria and mammals make the model pertinent (67,68).…”
Section: Selection Of Srnas and Construction Of Corresponding Mutantsmentioning
confidence: 99%